Effects of cotton–maize rotation on soil microbiome structure. (28th March 2021) - Xi, Hui; Zhang, Xuekun; Qu, Zheng; Yang, Dingyi; Alariqi, Muna; Yang, Zhaoguang; Nie, Xinhui; Zhu, Longfu
Abstract: Verticillium wilt is a disastrous disease in cotton‐growing regions in China. As a common management method, cotton rotation with cereal crops is used to minimize the loss caused by Verticillium dahliae . However, the correlation between soil microbiome and the control of Verticillium wilt under a crop rotation system is unclear. Therefore, three cropping systems (fallow, cotton continuous cropping, and cotton–maize rotation) were designed and applied for three generations under greenhouse conditions to investigate the different responses of the soil microbial community. The soil used in this study was taken from a long‐term cotton continuous cropping field and inoculated with V. dahliae before use. Our results showed that the diversity of the soil bacterial community was increased under cotton–maize rotation, while the diversity of the fungal community was obviously decreased. Meanwhile, the structure and composition of the bacterial communities were similar even under the different cropping systems, but they differed in the soil fungal communities. Through microbial network interaction analysis, we found that Verticillium interacted with 17 bacterial genera, among which Terrabacter had the highest correlation with Verticillium . Furthermore, eight fungal and eight bacterial species were significantly correlated with V. dahliae . Collectively, this work aimed to study the interactions among V. dahliae, the soil microbiome, and plant hosts, and elucidate the relationship between crop rotation and soil microbiome, providing a new theoretical basis to screen the biological agents that may contribute to Verticillium wilt control. Abstract : The effect of crop rotation on the soil fungal community is greater than that on the bacterial community, and the interaction between Verticillium dahliae and soil microbiome provides a theoretical basis for Verticillium wilt control.